Building Religious Moderation as a Strategy to Counter Intol-erance and Extremism in Indonesia - Luciana Haryanto; Timotius Sukarna (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This article aims to explain why ‘religious moderation’ is essential in preventing intolerance and extremism in Indonesia. This study employs a library research method, including books, journals, encyclopaedias, and dictionaries. The findings of this study indicate that ‘religious moderation’ has the potential to keep religious values relevant and meaningful over time. In conclusion, an important and aligned religious vision and mission can create beauty, peace, brotherhood, and unity in social diversity through ‘religious moderation’. Therefore, there is an urgent need to encourage ‘religious moderation’, namely: religion must be understood and applied to free humans from extreme attitudes and actions that can damage humanity. In this view, religion should not be used as a tool to justify destructive actions. Instead, religion should be a source of creative inspiration that can improve the quality of human life everywhere.